Una historia de amor y oscuridad - Oz, Amos, (Nuevos tiempos (Madrid, Spain) ;, 2012)
Amos Oz takes us on a journey through his childhood and adolescence, a quixotic child's-eye view along Jerusalem's wartorn streets in the 1940s and '50s, and into the infernal marriage of two kind, well-meaning people: his fussy, logical father, and his dreamy, romantic mother. Caught between them is one small boy with the weight of generations on his shoulders. And at the tragic heart of the story is the suicide of his mother, when Amos was twelve-and-a-half years old. Soon after, still a gawky adolescent, he left home, changed his name and became a tractor driver on a kibbutz." "'Jews go back to Palestine' the graffiti in 1930s Lithuania urged his family, so they went; then later the walls of Europe shout 'Jews get out of Palestine'. Oz's story dives into 120 years of family history and paradox, the saga of a Jewish love-hate affair with Europe that sweeps from Vilna and Odessa, via Poland and Prague, to Israel. Those who stayed in Europe were murdered; those who escaped took the past with them. In search of the roots of his family tragedy, he uncovers the secrets and skeletons of four generations of Chekhovian characters in this Tolstoyan drama. Meet the three sisters who got away; the old woman with a terrible fear of Levantine germs; the men who liked women, just a bit too much; cats in the classroom, bombs in the street, the dwarf in the department store; messianic kibbutzniks and self-important scholars. And be there on the night the UN said yes to Israel and his father cried; or the disastrous day a priggish little Jewish boy tried to impress a Palestinian girl. Farce and heartbreak, history and humanity make up this portrait of the artist who saw the birth of a nation, and came through its turbulent life as well as his own.